Genetic base of soybean (Glycine max) varieties released in India as revealed by coefficient of parentage - BHARADWAJ, CH; SATYAVATHI, C TARA; TIWARI, S P; KARMAKAR, P G (The Indian Journal of Agricultural Sciences, 2014)
Pedigrees of 66 varieties of soybean [Glycine max (L.) Merr.] released and notified in India during 1968-2000 were traced back to 76 ancestors. The fractional genetic contributions of these cultivars computed using coefficient of parentage (r) estimates, indicated an average ’r’ of 0.050 and 72.67% genetic contribution from as few as 10 ancestors. ’Bragg’ was the most frequently used ancestor and occurred as a direct parent in 15 of 66 pedigrees. Although more ancestors were: introduced in the recent breeding programmes, extensive use of superior or derived genotypes from the same pool explains why the integration of new germplasm did not result in the diversification of the released varieties. These results clearly revealed the narrow genetic base in current soybean varieties of India.